Urgensi bahasa arab di era digital: Menelisik tantangan dan potensi dalam konteks global - Anam, Rifky Khoirul (Maliki Interdisciplinary Journal, 2025)
Digitalization has fundamentally changed the global communication landscape, making mastery of diverse foreign languages an important prerequisite. In this context, Arabic holds a strategic position as the key to access to Islamic scholarship, a facilitator of international communication, and an economic opener in the dynamic Middle East region. This scholarly article examines the significance of Arabic in the digital age, uncovers the various challenges faced by its learners, and explores the potential and opportunities offered by technological advancements. The discussion includes barriers such as grammatical complexity and dialect variation, but also highlights solutions through the availability of abundant online learning resources, direct interaction with native speakers via social media, and the use of artificial intelligence. In the end, this article concludes that with a strategic approach and the use of technology, challenges can be overcome and the potential of the Arabic language can be maximized in this global era.